2014
DOI: 10.1007/s11864-014-0294-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mTOR Signaling Pathway in Neuroendocrine Tumors

Abstract: Opinion statementNeuroendocrine tumors (NETs) are a heterogeneous group of malignancies characterized by variable but most often indolent biologic behavior. Well-differentiated NETs can be broadly classified as either carcinoid or pancreatic NET. Although they have similar characteristics on routine histologic evaluation, the 2 tumor subtypes have different biology and respond differently to treatment, with most therapeutic agents demonstrating higher response rates in pancreatic NETs compared with carcinoid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 60 publications
(61 reference statements)
1
47
0
1
Order By: Relevance
“…Upregulation of mTOR signaling components[711], downregulation of its upstream negative regulators; phosphatase and tensin homolog deleted on chromosome 10 [PTEN] and tuberous sclerosis complex 2 [TSC2] [1214], and genomic mutation of mTOR pathway[15,16] in NETs were reported from numerous groups. The anti-proliferative effect of mTOR pathway inhibition was reported in preclinical models of NETs [12,17], and thus it was a promising therapeutic target[6,18]. The efficacy and safety of everolimus, an oral inhibitor of the mTOR pathway[19], in patients with advanced NETs of different origins was examined in a series of phase II/III clinical studies; RADIANT trials (Table 1) [20–23].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of mTOR signaling components[711], downregulation of its upstream negative regulators; phosphatase and tensin homolog deleted on chromosome 10 [PTEN] and tuberous sclerosis complex 2 [TSC2] [1214], and genomic mutation of mTOR pathway[15,16] in NETs were reported from numerous groups. The anti-proliferative effect of mTOR pathway inhibition was reported in preclinical models of NETs [12,17], and thus it was a promising therapeutic target[6,18]. The efficacy and safety of everolimus, an oral inhibitor of the mTOR pathway[19], in patients with advanced NETs of different origins was examined in a series of phase II/III clinical studies; RADIANT trials (Table 1) [20–23].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data suggest that the PI3K/AKT/mTOR pathway might be functionally relevant in the progression of PanNETs and indicate that it is an exciting setting to test PI3K/AKT/mTOR pharmacological intervention. Indeed, everolimus, an mTOR allosteric inhibitor is currently being used to treat patients with advanced PanNETs (5, 14, 15). A phase II clinical trial has showed efficacy of everolimus in metastatic PanNETs after failure of chemotherapy (5, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, all 4 cases demonstrated either a CNV alteration or a PTEN somatic mutation that would be predicted to activate the mTOR pathway. mTOR inhibitors are already used to treat other cancer types, including other neuroendocrine tumors, and may have clinical utility in patients with salivary high-grade NECs (Chan and Kulke, 2014;Dienstmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%